1988
DOI: 10.1099/0022-1317-69-6-1275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Conserved Region in Fowlpox Virus and Vaccinia Virus Genomes and the Translocation of the Fowlpox Virus Thymidine Kinase Gene

Abstract: SUMMARYThe DNA sequence of a clustered set of genes which are conserved in orthopoxviruses has been determined for the avipoxvirus, fowlpox virus. The arrangement of the genes in fowlpox virus is nearly identical to that in vaccinia virus, and genes which are overlapping in vaccinia virus overlap in fowlpox virus. One major difference exists however, as the thymidine kinase (TK) gene is absent in fowlpox virus from the position it occupies within this cluster of genes in vaccinia virus. Instead, in fowlpox vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…1 and 2a). The ORFs are situated in a tightly clustered configuration with a dominant direction of orientation similar to previously reported nucleotide sequences from various VV and FPV genomic regions (Drillien et al, 1987;Binns et al, 1988;Tomley et al, 1988;Niles et al, 1986;Rosel et al, 1986;Schmitt & Stunnenberg, 1988;Tamin et al, 1988;Kotwal & Moss, 1988, 1989Boursnell et al, 1988). Only two regions within the 10465 bp sequence have any significant stretches that lack potential ORFs.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…1 and 2a). The ORFs are situated in a tightly clustered configuration with a dominant direction of orientation similar to previously reported nucleotide sequences from various VV and FPV genomic regions (Drillien et al, 1987;Binns et al, 1988;Tomley et al, 1988;Niles et al, 1986;Rosel et al, 1986;Schmitt & Stunnenberg, 1988;Tamin et al, 1988;Kotwal & Moss, 1988, 1989Boursnell et al, 1988). Only two regions within the 10465 bp sequence have any significant stretches that lack potential ORFs.…”
Section: Discussionsupporting
confidence: 80%
“…From the nucleotide sequence provided in this communication and others reported previously (Drillien et al, 1987;Binns et al, 1988;Tomley et al, 1988), it is apparent that FPV and VV are closely related in at least some genomic regions. Previous reports have found that FPV contains a genomic region closely related to a portion of the VV HindlII J region (Drillien et al, 1987;Binns et al, 1988).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The sequence TTTTTTT, 14 nt downstream of the L2R gene, is a subset of TTTTTNT which controls termination of transcription in VV early genes. The presence of VV-like early transcription termination sequences just downstream of early FPV genes has been described by others as well (Kumar & Boyle, 1990a, b;Binns et al, 1988).…”
Section: Discussionmentioning
confidence: 62%